Radiosensitivity of microorganisms in Saengshik products and irradiation effects on the sensorial properties. (November 2018) - Kim, Gui-Ran; Ramakrishnan, Sudha Rani; Kwon, Joong-Ho
Abstract: Saengshik products usually include powders of plant-derived foods that are normally non-heated and thus have inherent limitations in microbial control. Here, we investigated the microbial reduction and sensorial properties of two types of Saengshik products commercially available in Korean markets after electron-beam and gamma-ray irradiation (0, 1, 3, 5, and 10 kGy). The initial microbial loads in the products were 6–7 log colony-forming units (CFU)/g of total aerobic bacteria (TAB), 4–5 log CFU/g of yeasts and molds (YM), and ≤ 3 log CFU/g of coliforms. Radiosensitivities (D10 values) of TAB, YM, and the indicator pathogens Clostridium perfringens and Bacillus cereus were 1.21–1.86 kGy, 1.03–1.97 kGy, 0.42–0.48 kGy and 0.58–0.68 kGy, respectively, regardless of the radiation source or product type. Radiation 5D values for both pathogens were 2.10–3.40 kGy, which is the dose needed to achieve the recommended 5-log reduction. The radiation sensitivity (D10 and 5D values) was higher in B. cereus than in C. perfringens for both samples. Irradiation up to 10 kGy induced negligible changes in sensory scores for the Saengshik samples (p > 0.05). An electronic nose effectively distinguished the flavor profiles of irradiated products between 10 kGy and ≤ 5 kGy approved by the Korean Food Code for Saengshik ingredients. These results indicate that 5 kGy irradiation with electron-beam or gamma-ray was sufficient for achieving microbial control in powdered Saengshik products. Highlights: Radiosensitivity of microorganisms in Saengshik products was studied. Irradiation > 9 kGy is needed for 5-log decrease in aerobic bacteria, yeasts, and molds. D10 values of C. perfringens and B. cereus were 0.48 and 0.68 kGy, respectively. Dose up to 10 kGy induced negligible changes in sensory attributes of Saengshik .